How to train your dragon - Activision Pub., Inc.; DreamWorks Animation (Los Angeles, CA : Activision Pub., 2010)
Battle your friends in this all-new adventure, based on the world of DreamWorks Animation's latest movie, How to Train Your Dragon. With countless ways to customize, you'll design the coolest dragons to ever live on the Island of Berk. Explore this epic world as Hiccup or Astrid in Adventure Mode or experience fierce battle action in Arena Mode as you fight, fly, and fire your way to victory!
Title from container.
1-2 players.
"Xbox live"--Container.
System requirements: Xbox 360; 572 KB to save game; HDTV 720p/1080i/1080p; in-game Dolby Digital.
Keywords: Dragons; Xbox video games; Computer adventure games